Basal rot of Chamelaucium uncinatum caused by Phytophthora nicotianae in Argentina - Palmucci, Hemilse Elena (2013)
Fil: Palmucci, Hemilse Elena. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.